The Role of Teacher Mover as Teacher Leadership at The State Elementary School of Ulujami District, Pemalang Regency: At The State Elementary School Of Ulujami District, Pemalang Regency - Istikomah; Lela Iman Ningrum; Yuli Anggraeni; Nurkolis (LPPM Universitas PGRI Semarang, 2024)
There is a new paradigm and a curriculum that is constantly changing with technological developments, the role of teachers is required to follow these developments. One of the government's efforts in realizing educators who have competence to achieve national education goals is the Program Pendidikan Guru Penggerak (PPGP). Through PPGP, many teacher mover (guru penggerak) throughout Indonesia are graduated who are ready to enter schools and are expected to have a significant impact on schools and the education ecosystem. This study aims to identify the role of teacher mover as teacher leadership in improving the quality of schools at the state elementary school Ulujami District, Pemalang Regency. This study uses qualitative research with a descriptive approach. Data collected from a combination of literature studies, observations, and interviews were systematically analyzed to identify the role of teacher leaders as Teacher Leadership in improving school quality. The results of the study show that the role of teacher mover has an important contribution to teacher leadership in State Elementary Schools in Ulujami District, Pemalang Regency. The role of teacher mover includes being a learning leader, being a coach for others, encouraging collaboration, realizing student leadership, and mobilizing the community of practitioners. The advice given by the author to the teacher mover is to always actively carry out self- development, increase cooperation with various parties, collaborate with school residents and the community of teacher mover, and maintain self- motivation to become teacher leadership.